A new Indian species of Pardoteleia Kozlov & Lê (Hymenoptera: Scelionidae: Scelioninae) and first description of the male - Kamalanathan, Veenakumari; Mohanraj, Prashanth (Zootaxa, 2016)
Pardoteleia, a monotypic genus was described by Kozlov and Lê (1988). A new species Pardoteleia flava from India is now described and imaged. The hitherto unknown male of this genus is also described and imaged for the first time. Pardoteleia prater, the type species is redescribed and imaged with intraspecific variations in the Indian specimens.